First Record of Two Longicorn Beetles (Insecta: Coleoptera: Cerambycidae: Lamiinae) from Kerala with Redescription - Sreedharan Namboodiri, M. P.; Ghosh, S. M. (Indian Forester, 2020)
The longicorn beetles belong to the family Cerambycidae attack cash crops and freshly felled log woods. Their taxonomic studies in Kerala are less known. Out of four subfamilies so far reported from Kerala viz. Prioninae, Lepturinae, Cerambycinae and Lamiinae, Lamiinae are the most abundant. Among these Lamiids, Acalolepta nivosa (White, 1858) and Apriona germari (Hope, 1831) are recorded for the first time from Kerala. The present study includes their redescription, distributional data and pest status.